POTENTIAL FISHERY SECTOR TO THE WELFARE OF THE COMMUNITY IN THE PERSPECTIVE OF MAQASID SYARI'AH: Case Study Of People Around Jobokuto Fish Auction Site In Ujung Batu Village, Jepara City, Central Java - Ahmad Lukman Nugraha; Azizah Zawaj (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2022)
Jepara Regency is located at the northern end of Java Island, astronomically Jepara Regency is located between 50 43 ' 20.67